Macronutrient, nutritional status, and anemia incidence in adolescents at Islamic boarding school - Kartika Pibriyanti; Lola Zahro; Safira Kholifatul Ummah; Lulu’ Luthfiya; Fitri Komala Sari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Background: Anemia occurs due to the body's loss of red blood cells and decreased iron absorption. Globally, it is known that the prevalence of anemia is 1.62 billion, with the majority of anemia sufferers being a group of women who are not pregnant, as many as 468.4 million people. In addition, the highest prevalence of anemia in the group of school-age girls is 47.4%, while in men, only 12.7%.Objective: This study aims to determine the correlation between macronutrients and nutritional status with the anemia accident in adolescents at Islamic Boarding schools.Methods: This study used a case-control design with matching criteria aged 15-19 years, not menstruating, not fasting. Sampling with quota sampling of late adolescents with a population of 15-19 years 1,359 people, anemic case sample of 46 people and control without anemia 46 people, intake questionnaire using the SQ-FFQ, statistical test with Chi-Square.Results: There was a significant relationship between macronutrient intake [energy p=0.048; OR=3.3 (CI 0.965-11.28), protein p=0.036; OR=3.98 (CI 1.018-15.57)] and nutritional status [p=0.024; OR=5.35 (CI 1.088-26.32)] with anemia incidence. Less energy intake has a risk of 3.3 times anemia, lack of protein intake has a risk of 3.98 times, and malnutrition has a risk of anemia of 5.35 times.Conclusions: There was a significant correlation between energy, protein intake, and nutritional status with anemia incidents. Nutritional status has the strongest association with anemia. * Presented at the International Nutrition and Health Symposium (INHESION) on Sunday, November 15th, 2020, in Yogyakarta, organized by HIMAGIKA and the Department of Health Nutrition, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada